Hemoglobin Agenogi - A rare abnormal beta globin chain variant - Sunita Sharma; Geetika Sharma; Jagdish Chandra; Roshan Colah (Wolters Kluwer Medknow Publications, 2016)
Haemoglobin (Hb) Agenogi is clinically asymptomatic, rare β-globin chain variant characterized by a substitution of glutamic acid by lysine at position 90 of β-chain. It elutes in the C-window on high-performance liquid chromatography (HPLC). We report a 10-year-old male with easy fatigability, lethargy, pallor, and mild splenomegaly. Hematological parameters revealed microcytic hypochromic anemia and mildly raised red blood cells count, suggestive of thalassemia trait. On HPLC, a predominant peak was observed in the C-window (82.6%) along with raised HbA 2 level (9.3%). Based on these findings, a possibility of HbC disease/β-thalassemia trait doubly heterozygous was considered. Family studies were advised. HPLC findings in father were suggestive of β-thalassemia trait, while both his mother and brother had an abnormal peak in the C-window of 42.7% and 40.8%, respectively, with elevated HbA 2 values of 5% and 4.9%, respectively. Direct DNA sequencing revealed intervening sequences 1-5 (G ; C) in father, confirming β-thalassemia trait. His mother and brother had heterozygous gene mutation at codon 90 of β-globin chain (G ; A) suggestive of Hb Agenogi. The child carried mutations for both β-thalassemia trait as well as Hb Agenogi.